Computational Study of a Novel Compound with Thioether-Bridge - Sen, Fatih; Cukurovali, Alaaddin; Sert, Yusuf (Taylor & Francis Ltd, 2023)
An investigation into the properties of the novel compound with thioether-bridge 2-((4,5-di-p-tolyl-4H-1,2,4-triazol-3-yl)thio)-1-mesitylethanone by use of single-crystal X-ray diffraction (SCXRD), FT-IR, and nuclear magnetic resonance spectroscopy and density functional theory calculations. The X-ray crystallographic data, which reveal the molecular and crystal structure, have been collected in the 2.98-26.27 theta range at 296 K. Then, Hirshfeld surface analyses were performed over the crystal structure and possible hydrogen bondings were indicated. In addition to the determination of the structure, characteristic vibrational modes, chemical shifts (H-1 and C-13), and theoretical highest occupied molecular orbital-lowest unoccupied molecular orbital and UV analysis in four different solvents were evaluated. The structural and spectral results were compared with the corresponding quantum chemical calculations. The experimental and theoretical (calculated) data exhibited good harmony. Additionally, Natural Bonding Orbital and Mulliken charge analyses were investigated. Then, the molecular docking of the title ligand within the Protein Data Bank: 2IJ5 protein was evaluated according to interaction shapes. Lastly, drug-likeness and ADME features of the title molecule were evaluated.
Keywords: 124-Triazol; DFT calculations; IR; molecular docking; thioether; X-ray